2012
DOI: 10.1590/s0100-40422012000500022
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and selectivity improvement in doping analysis using comprehensive two-dimensional gas chromatography coupled with time-of-flight mass spectrometry

Abstract: Recebido em 5/9/11; aceito em 21/11/11; publicado na web em 31/1/12Comprehensive two-dimensional gas chromatography coupled with time-of-flight mass spectrometry was used for the identification of forty doping agents. The improvement in the specificity was remarkable, allowing the resolution of analytes that could not be done by one-dimensional chromatographic systems. The sensitivity observed for different classes of prohibited substances was clearly below the value required by the World Anti-Doping Agency. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Barbosa et al used a similarly complex heating program to successfully separate 40 doping agents (from different pharmacological classes) and their metabolites. [33] This included AAS and their metabolites (S1, including clenbuterol, designated an 'other anabolic agent'), β2-agonists (S3), aromatase inhibitors and selective estrogen receptor modulators (both S4, Hormone and Metabolic Modulators), diuretics & masking agents (S5), stimulants (S6), narcotics (S7) and cannabinoids (S8) plus a drug used for the enhancement of oxygen uptake, transport or delivery (prohibited methods category 'M1'). However, the authors purposefully worked at a concentration 10 times higher than the WADA MRPL (for steroids) as their intention for this article was to highlight the improvement in resolution and sensitivity rather than detection limits, which they suggested had been demonstrated in other papers.…”
Section: S1 -Anabolic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Barbosa et al used a similarly complex heating program to successfully separate 40 doping agents (from different pharmacological classes) and their metabolites. [33] This included AAS and their metabolites (S1, including clenbuterol, designated an 'other anabolic agent'), β2-agonists (S3), aromatase inhibitors and selective estrogen receptor modulators (both S4, Hormone and Metabolic Modulators), diuretics & masking agents (S5), stimulants (S6), narcotics (S7) and cannabinoids (S8) plus a drug used for the enhancement of oxygen uptake, transport or delivery (prohibited methods category 'M1'). However, the authors purposefully worked at a concentration 10 times higher than the WADA MRPL (for steroids) as their intention for this article was to highlight the improvement in resolution and sensitivity rather than detection limits, which they suggested had been demonstrated in other papers.…”
Section: S1 -Anabolic Agentsmentioning
confidence: 99%
“…Barbosa et al used this model to accelerate their initial optimisation. [33] GCxGC-MS for steroid analysis is not just confined to biological matrices. Other research reported includes wastewater [44,45] and coconut [46] / vegetable oils.…”
Section: S1 -Anabolic Agentsmentioning
confidence: 99%